Our Materia Medica, Repertory, Miasmas in Homoeopathy and You as Homoeopaths(!). Where do You Stand between Failures and Successes? Does it Require Research Work ? Yes. How? Who? When? How ... Hence Forth! (Advancements in Homeopathic Research, 2022)
At present our MATERIA MEDICA of Homoeopathy is a “Mixed Bag” of signs and symptoms of drugs / medicines. We have in it - wanted and unwanted symptoms and signs. What we need is “what is curative in medicines?” for “what is curable in diseases (6, para. 3)?” which is not there. It contains proved, unproved, assumative, unauthenticated, unverified, imaginative, speculative, figurative, picturised, hypothetical, false conjectures and fictions, mis-interpreted, hallucinative, illusionary, delusionary, dreamy, abstract, pathological, poisoned and poisoning, emperical and theoretical, and of opinions - a CHAOS. A dilemma - of students, beginners and practitioners failures.
Keywords: Homoeopathy; Failures and Successes; Research Work; MATERIA MEDICA